Isolation and characterization of partial genomic sequence of cellulose synthase (CesA) gene from Batai (Paraserianthes falcataria) - Shyamala Devi, Asohan (Universiti Malaysia Sarawak (UNIMAS), 2015)
Paraserianthes falcataria or locally known as batai has been widely used in the production of timber-based products such as plywood, furniture and light-weight construction materials. Recently, P. falcataria has been reported to show highest level of cellulose enzymatic hydrolysis and bioethanol production. Therefore, in order to obtain a better quality of cellulose, it is crucial to identify and isolate the cellulose synthase (ChesA) gene which is directly involved in the cellulose biosynthesis.